A complementary chemical probe approach towards customized studies of G-quadruplex DNA structures in live cells. Issue 8 (7th February 2022) - Prasad, Bagineni; Doimo, Mara; Andréasson, Måns; L'Hôte, Valentin; Chorell, Erik; Wanrooij, Sjoerd
Abstract : The development of an approach to generate multiple tailored biochemical tools based on the same core structure, Phen-DC3, to advance studies of G4 biology to uncover molecular details and therapeutic approaches. Abstract : G-quadruplex (G4) DNA structures are implicated in central biological processes and are considered promising therapeutic targets because of their links to human diseases such as cancer. However, functional details of how, when, and why G4 DNA structures form in vivo are largely missing leaving a knowledge gap that requires tailored chemical biology studies in relevant live-cell model systems. Towards this end, we developed a synthetic platform to generate complementary chemical probes centered around one of the most effective and selective G4 stabilizing compounds, Phen-DC3. We used a structure-based design and substantial synthetic devlopments to equip Phen-DC3 with an amine in a position that does not interfere with G4 interactions. We next used this reactive handle to conjugate a BODIPY fluorophore to Phen-DC3. This generated a fluorescent derivative with retained G4 selectivity, G4 stabilization, and cellular effect that revealed the localization and function of Phen-DC3 in human cells. To increase cellular uptake, a second chemical probe with a conjugated cell-penetrating peptide was prepared using the same amine-substituted Phen-DC3 derivative. The cell-penetrating peptide conjugation, while retaining G4 selectivity and stabilization, increased nuclear localization and cellular effects, showcasing the potential of this method to modulate and direct cellular uptake e.g. as delivery vehicles. The applied approach to generate multiple tailored biochemical tools based on the same core structure can thus be used to advance the studies of G4 biology to uncover molecular details and therapeutic approaches.